Product Becomes Sum

Find the value of n>1 for this equation : n ! = n ( n + 1 ) 2 { n!\quad }=\quad \frac { n(n+1) }{ 2 }


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

n ( n + 1 ) 2 \frac { n(n+1) }{ 2 } is the formula for triangular numbers i.e. the sum of integers from 1 1 to n n .

n ! n! is the notation for the product of integers from 1 1 to n n .

n ! > n ( n + 1 ) 2 n! > \frac { n(n+1) }{ 2 } when n > 3 n > 3 because 4 ! = 24 > 10 = 4 ( 4 + 1 ) 2 4! = 24 > 10 = \frac { 4(4+1) }{ 2 } and adding integers greater than 1 would always result in a smaller result than if you multiplied integers greater than 1 (with the exception of 2 * 2 and 2+2).

Therefore, n = 1 , 2 o r 3 n = 1, 2 or 3

If n = 1 n = 1 then 1 ! = 1 1! = 1 and 1 ( 1 + 1 ) 2 = 1 \frac { 1(1+1) }{ 2 } = 1 . Therefore, n = 1 n = 1

If n = 2 n = 2 then 2 ! = 2 2! = 2 and 2 ( 2 + 1 ) 2 = 3 \frac { 2(2+1) }{ 2 } = 3 . Therefore, n n is not 2 2

If n = 3 n = 3 then 3 ! = 6 3! = 6 and 3 ( 3 + 1 ) 2 = 6 \frac { 3(3+1) }{ 2 } = 6 . Therefore, n = 3 n = 3

Therefore n = 1 n = 1 and 3 3

Maybe try using induction to prove your assertion that n ! > 1 2 n ( n + 1 ) n > 3 \ n! > \frac{1}{2} n(n+1) \ ~ \forall \ n >3 . still, a neat solution :)

Curtis Clement - 5 years, 9 months ago

Nice solution! Upvoted!

Arulx Z - 5 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...